1972
DOI: 10.1111/j.1432-1033.1972.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Antigenic Determinants on Bovine Encephalitogenic Protein

Abstract: By peptic or tryptic proteolysis of different fragments of bovine encephalitogenic protein, a set of small fragments covering the following regions of the native protein have been obtained: 44-68, 44-89, 75-91, 93-116, 114-130, 134-150, and 154-170 (the amino acid residues are numbered according to [l]). These fragments were used in the macrophage migration inhibition technique in guinea pigs (an assay which is vividly considered as a correlate in vitro to delayed type hypersensitivity) to study the localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…These cleavages have been shown previously to occur at relatively high pepsin/substrate ratios (Carnegie, 1971;Eylar et al, 1971;Bergstrand, 1972).…”
Section: Discussionsupporting
confidence: 56%
“…These cleavages have been shown previously to occur at relatively high pepsin/substrate ratios (Carnegie, 1971;Eylar et al, 1971;Bergstrand, 1972).…”
Section: Discussionsupporting
confidence: 56%
“…Guinea pigs and Lewis rats immunized with shark MBP , and guinea pigs immunized with dogfish MBP (Agrawal et al, 1971), have previously been reported to show no evidence of EAE. Since MBP has several antigenic determinants (Hruby et al, 1985) it is possible that the observed cellular immunity is directed toward a part of the antigen that is not involved in the induction of EAE in guinea pigs (Bergstrand, 1972;Spitler et al, 1972;Bergstrand and Kallen, 1973).…”
Section: F L Tai Et Almentioning
confidence: 99%
“…Fragment 93-170 was isolated directly from the acid extract of defatted bovine brain tissue (Bergstrand, submitted, c.f. [ 15,211) and an aliquot of the purified peptide was reacted with HNB-Br according to the method of Barman and Koshland [22] to give fragment HNB-93-170. The degree of substitution was determined to 1.2 HNB-residues/tryptophan residue.…”
Section: Peptide Fragments Of the Encephalitogenic Proteinmentioning
confidence: 99%
“…The results of these examinations, except for those concerning peptides 154-168 and 154-1 69, have been given in appropriate reports. In previous publications [12][13][14][15]19, 2 11 the nomenclature of some of the peptides differs from that presently used. Previously, peptides 44-89,tyr, 44-68, tyr, 44-11 6,tyr, 1 17-170,tyr, and 134-150,tyr were referred to as solely 44-89,44-68,44-116, 117-170 and 134-150, respectively.…”
Section: Peptide Fragments Of the Encephalitogenic Proteinmentioning
confidence: 99%
See 1 more Smart Citation